Lidar Observation of Tropopause Ozone Profiles in the Equatorial Region - Shibata Yasukuni; Nagasawa Chikao; Abo Makoto (EPJ Web of Conferences, 2016)
Tropospheric ozone in the tropics zone is significant in terms of the oxidizing efficiency and greenhouse effect. However, in the upper troposphere, the ozone budget in the tropics has not been fully understood yet because of the sparsity of the range-resolved observations of vertical ozone concentration profiles. A DIAL (differential absorption lidar) system for vertical ozone profiles have been installed in the equatorial tropopause region over Kototabang, Indonesia (100.3E, 0.2S). We have observed large ozone enhancement in the upper troposphere, altitude of 13 - 17 km, concurring with a zonal wind oscillation associated with the equatorial Kelvin wave around the tropopause at equatorial region.